Estimation of crustal vertical movements due to atmospheric loading effects by GPS observations - Rodrigues,Erica Patias (2007)
The objective of this paper is the estimation of vertical movements of the Earth's crust using data of 45 GPS permanent stations network situated in Europe and North of Asia (Siberia). First, daily positions are calculated with the GAMIT processing GPS data software, developed in the Massachusetts Institute of Technology, for a period of approximately 500 days (November and December 2000, the entire year of 2001 and January and February of 2002). Each daily solution is stabilized in a reference frame with the implication of a similitude transformation in the GLOBK software, also developed in the MIT, with the Kalman filter. The crust deforms vertically due to different phenomena (earthquakes, landslides¼). We focused in this project the effects caused by the atmospheric loading, it means the effects of the weight of the air's column which surrounds the GPS stations. This loading is calculated for a 2.5º × 2.5º resolution grid, with meteorological data provided of ECMWF (European Centre for Medium-range Weather Forecasts). The amplitude of these loadings is in the order of few millimetres up to 3 centimetres (Schuh et al., 2003). Finally we compare the vertical GPS permanent stations positions with the vertical movements of the Earth's crust due to atmospheric loading. We observed for some sites in Siberia a predominant effect during winter in the vertical component. For example, for IRKT station (Irkust, Russia) the correlation value for the year of 2001 is 0.61.